Benjaminian Reminiscences in Deleuze’s and Daney’s Dialogue about Images in Control Societies - Wiame, Aline (Estudios de Filosofía, 2024)
This article examines Gilles Deleuze’s 1986 letter to French film critic Serge Daney about cinema, television, and images in control societies through a Benjaminian lens. While neither Deleuze nor Daney deeply engage with Walter Benjamin’s thought, I argue that the ideas or dialectical images constructed by the German thinker are crucial to better understand Deleuze’s and Daney’s thoughts regarding the threatened death of modern cinema in the 1980s because of the predominance of television as a control apparatus. In the first part of the article, I analyze the aesthetical and political meaning of the concept of history as/of perception. I also show affinities between Benjamin’s and Deleuze’s works through their connection to art historian Aloïs Riegl. In the sec- ond part, I demonstrate how Deleuze’s and Daney’s reflections about mannerism as a weapon against the rise of clichés and the ideology of the visible in control societies must be supplemented by Benjamin’s concept of “construction”. In conclusion, I draw on Benjamin’s discussion of politics as a body space to advocate for desiring mannerisms to fight control apparatuses and the reign of clichés.